2022
DOI: 10.34133/2022/9852518
|View full text |Cite
|
Sign up to set email alerts
|

Distribution- and Metabolism-Based Drug Discovery: A Potassium-Competitive Acid Blocker as a Proof of Concept

Abstract: Conventional methods of drug design require compromise in the form of side effects to achieve sufficient efficacy because targeting drugs to specific organs remains challenging. Thus, new strategies to design organ-specific drugs that induce little toxicity are needed. Based on characteristic tissue niche-mediated drug distribution (TNMDD) and patterns of drug metabolism into specific intermediates, we propose a strategy of distribution- and metabolism-based drug design (DMBDD); through a physicochemical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Namely, this aromatic ring docked to the active site of the gastric proton pump and contributed significantly to the stabilization of the ligand-protein complex by forming the additional interactions with LEU141 (π-σ), ALA335 (π-alkyl), VAL338 (π-alkyl), and CYS813 (π-sulfur) (Figures 7B and 12). In the aforementioned study of Wang and co-workers (20), the pyrrole derivative SH-337 demonstrated very similar binding orientiation compared to our tested compounds. Namely, nitrogen atom of the aliphatic amine formed two donor hydrogen bonds with carbonyl oxygen atoms of residues GLU795 and GLU343.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Namely, this aromatic ring docked to the active site of the gastric proton pump and contributed significantly to the stabilization of the ligand-protein complex by forming the additional interactions with LEU141 (π-σ), ALA335 (π-alkyl), VAL338 (π-alkyl), and CYS813 (π-sulfur) (Figures 7B and 12). In the aforementioned study of Wang and co-workers (20), the pyrrole derivative SH-337 demonstrated very similar binding orientiation compared to our tested compounds. Namely, nitrogen atom of the aliphatic amine formed two donor hydrogen bonds with carbonyl oxygen atoms of residues GLU795 and GLU343.…”
Section: Discussionsupporting
confidence: 66%
“…On the other hand, Wang and co-workers designed the molecule SH-337, using very similar distribution-based approach as in our study. Molecule SH-337 had a logD7.4 value of 1.3 and a pKa of 9.0 and demonstrated the significantly lower value of docking score (-11.53 kcal/mol) compared to the tested compounds (20).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation